Divide (m^2 - 14m - 32) by (m+2)

Given

m2 – 14m – 32

On factorising, we get,

= m2 – 16m + 2m – 32

= m(m – 16) + 2(m – 16)

We get,

= (m – 16) (m + 2)

Now, divide by (m+2)

m2 – 14m – 32 ÷ (m + 2)

= (m – 16) (m + 2) / (m + 2)

we get,

= (m – 16)

Was this answer helpful?

 
   

0 (0)

(1)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question